2013
DOI: 10.1075/scl.59.07rez
|View full text |Cite
|
Sign up to set email alerts
|

Competing target hypotheses in the Falko corpus

Abstract: Error annotation is a key feature of modern learner corpora. Error identification is always based on some kind of reconstructed learner utterance (target hypothesis). Since a single target hypothesis can only cover a certain amount of linguistic information while ignoring other aspects, the need for multiple target hypotheses becomes apparent. Using the German learner corpus Falko as an example, we therefore argue for a flexible multi-layer stand-off corpus architecture where competing target hypotheses can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 0 publications
0
15
0
1
Order By: Relevance
“…Rosen et al (2014) (see also its discussion in Meurers, 2015) have shown that differing target hypotheses among annotators account for a considerable amount of disagreement in the choice of error tags. They conclude, in line with Reznicek et al (2013), that an explicit target hypothesis is required for annotating learner errors. While target hypotheses in general are said to be hard to agree on (Lüdeling, 2008;Fitzpatrick and Seegmiller, 2004), minimal target hypotheses, i.e.…”
Section: Introductionmentioning
confidence: 65%
See 4 more Smart Citations
“…Rosen et al (2014) (see also its discussion in Meurers, 2015) have shown that differing target hypotheses among annotators account for a considerable amount of disagreement in the choice of error tags. They conclude, in line with Reznicek et al (2013), that an explicit target hypothesis is required for annotating learner errors. While target hypotheses in general are said to be hard to agree on (Lüdeling, 2008;Fitzpatrick and Seegmiller, 2004), minimal target hypotheses, i.e.…”
Section: Introductionmentioning
confidence: 65%
“…Two German L2 learner corpora are annotated with more than one target hypothesis: Falko (Reznicek et al, 2012) and EAGLE (Boyd, 2010). Falko treats orthographic and grammatical errors together at the first layer, though, and semantic/stylistic errors on the second.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations